THE SYSTEM OF PRACTICAL AND EVOLUTIONARY FORMATION OF LITERARY CONCEPTS IN PRIMARY SCHOOL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to the problem of the formation of literary concepts in pupils in primary school reading lessons. In it, the main difficulty in the formation of literary concepts in the primary classes is explainedchiliklar, the issues of their spelling. The article highlights the system of practical and evolutionary formation of literary concepts in primary school students.